Mitochondrial glycerol 3‐phosphate dehydrogenase promotes skeletal muscle regeneration. Issue 12 (2nd November 2018) - Liu, Xiufei; Qu, Hua; Zheng, Yi; Liao, Qian; Zhang, Linlin; Liao, Xiaoyu; Xiong, Xin; Wang, Yuren; Zhang, Rui; Wang, Hui; Tong, Qiang; Liu, Zhenqi; et al.
Abstract: While adult mammalian skeletal muscle is stable due to its post‐mitotic nature, muscle regeneration is still essential throughout life for maintaining functional fitness. During certain diseases, such as the modern pandemics of obesity and diabetes, the regeneration process becomes impaired, which leads to the loss of muscle function and contributes to the global burden of these diseases. However, the underlying mechanisms of the impairment are not well defined. Here, we identify mGPDH as a critical regulator of skeletal muscle regeneration. Specifically, it regulates myogenic markers and myoblast differentiation by controlling mitochondrial biogenesis via CaMKKβ/AMPK. mGPDH −/− attenuated skeletal muscle regeneration in vitro and in vivo, while mGPDH overexpression ameliorated dystrophic pathology in mdx mice. Moreover, in patients and animal models of obesity and diabetes, mGPDH expression in skeletal muscle was reduced, further suggesting a direct correlation between its abundance and muscular regeneration capability. Rescuing mGPDH expression in obese and diabetic mice led to a significant improvement in their muscle regeneration. Our study provides a potential therapeutic target for skeletal muscle regeneration impairment during obesity and diabetes. Synopsis: mGPDH is here identified as an important regulator of muscle differentiation and regeneration. Activation of the mGPDH/AMPK/mitochondrial biogenesis pathway provides a new strategy for improving muscle frailty. Direct targeting of mGPDH may also have therapeutic benefits for obesity and diabetes. mGPDH improves skeletal muscle regeneration by promoting myoblast differentiation. mGPDH promotes myoblast differentiation via CaMKKβ/AMPK control of mitochondrial biogenesis. mGPDH expression was reduced in skeletal muscle obtained from patients and animal models of obesity and diabetes. Rescuing mGPDH deficiency improves skeletal muscle regeneration during these pathological processes. Abstract : mGPDH is here identified as an important regulator of muscle differentiation and regeneration. Activation of the mGPDH/AMPK/mitochondrial biogenesis pathway provides a new strategy for improving muscle frailty. Direct targeting of mGPDH may also have therapeutic benefits for obesity and diabetes.